MUSIC OF AFRICA SERIES No. 17 No. 18 No. 19. All recorded and presented by Hugh Tracey. “More African Stories” - GALP. 1111; “Music from the Roadside - South Africa” - GALP. 1110; “Songs from the Roadside - Rhodesia” - GALP. 1113. - Kingslake, Brian (International Library of African Music, 1961)
pages: 114
Keywords: South Africa; African Music; Rhodesia; Zimbabwe